Ceramic-on-Ceramic Bearings in Total Joint Arthroplasty. Part 1 - Zazirnyi, I.M. (TERRA ORTHOPAEDICA, 2022)
Summary. Ceramic bearings were first employed as alternatives to polyethylene (PE) bearings in total joint arthroplasty about a decade after Sir John Charnley introduced the first durable total hip arthroplasty (THA) with a metal-PE articulation. Charnley’s approach was based on a metal stem bonded to bone with polymethylmethacrylate (PMMA) and an acetabular component made of ultra-high-molecular-weight PE (UHMWPE). Microscopic particulate debris in the joint space from bearing wear has been shown to lead to periprosthetic inflammation, osteolysis, and implant loosening. Cross-linking can reduce the wear of UHMWPE, but it also compromises UHMWPE’s mechanical properties. Accordingly, there are concerns related to potential brittleness if UHMWPE implants are not positioned optimally. Also, the smaller particles generated from cross-linked UHMWPE may present an increased particulate load in vivo. Thus, there is a need for data on the long-term outcomes of cross-linked UHMWPE. Any technology that can reduce bearing wear rates in THA and total knee arthroplasty (TKA) can potentially decrease the morbidity and risks associated with premature revision surgery related to wear. Improved wear resistance also allows the use of large-diameter femoral heads in THA, leading to increased arc of movement and less risk of prosthesis dislocation. The ideal joint bearing for THA and TKA would be able to withstand high cyclic loading for several decades without undergoing corrosion or fretting at modular metal tapers, and would possess proven biocompatibility and material stability in vivo, as well as ultralow wear rates. The search for the ideal total joint bearing has led to the development of ceramic bearings.